2013
DOI: 10.1021/cb400067g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Promiscuous Inhibitor Susceptibility of Escherichia coli LpxC

Abstract: The LpxC enzyme in the lipid A biosynthetic pathway is one of the most promising and clinically unexploited antibiotic targets for treatment of multidrug-resistant Gram-negative infections. Progress in medicinal chemistry has led to the discovery of potent LpxC inhibitors with a variety of chemical scaffolds and distinct antibiotic profiles. The vast majority of these compounds, including the nanomolar inhibitors L-161,240 and BB-78485, are highly effective in suppressing the activity of E. coli LpxC (EcLpxC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Analysis by Lee et al . suggested that Eco_LpxC exhibits significantly greater plasticity in the active site with greater potency for a variety of ligands in contrast to the relative potency against the LpxC enzyme from other pathogens . Ultimately, the consistency between Aae_LpxC structures suggested imposing constraints for modeling the reaction in this study was reasonable.…”
Section: Discussionmentioning
confidence: 72%
“…Analysis by Lee et al . suggested that Eco_LpxC exhibits significantly greater plasticity in the active site with greater potency for a variety of ligands in contrast to the relative potency against the LpxC enzyme from other pathogens . Ultimately, the consistency between Aae_LpxC structures suggested imposing constraints for modeling the reaction in this study was reasonable.…”
Section: Discussionmentioning
confidence: 72%
“…In 2002, British Biotech, now Vernalis, developed the sulfonamide BB-78485, which proved very active in vitro against E. coli (MIC = 1 μg mL −1 ) and having inhibitory potency against the E. coli LpxC enzyme in the nanomolar range (K i = 160 nm). [52] Importantly, comparison of the two E. coli structures with the corresponding one of the P. aeruginosa LpxC enzyme in complex with BB-78485 (PDB entry 2VES, [53] 1.9Å) revealed significant differences in the plasticity in the substrate-covering loop of the two enzymes that might account for their distinct inhibitory activity against P. aeruginosa versus E. coli. This lack of activity proved to be an issue, and the molecular bases that explain this poor efficacy in this pathogen were finally identified with the resolution of their enzyme/inhibitors complexes.…”
Section: The Lpxc Enzymementioning
confidence: 99%
“…[54][55][56][57] The most relevant examples are: i) the 4-(phenylethynyl)benzamide derivatives LPC-004 and CHIR-090, [58,59] the 4-(phenylbuta-1,3-diyn-1-yl)benzamide derivatives LPC-009 and LPC-011, [60] all of which were developed by Chiron and the University of Washington; ii) the difluoromethyl derivative LPC-058 developed by C. -J. Lee et al; [61] iii) the pyridine methylsulfone LpxC-4 (PF-5081090), [62,63] which was discovered by Pfizer; and iv) the cyclopropane derivative ACHN-975 [56] developed by Achaogen (Figure 5). Diverse crystal structures of the LpxC enzyme from different species, including P. aeruginosa, [59,63,[65][66][67][68][69] Aquifex aeolicus, [67,[70][71][72][73][74][75] Yersinia enterocolitica [76] and E. coli, [52,77] have been solved, either as an apo-form or in complex mainly with inhibitors and these structures provide a good understanding at the molecular level of the differences in the inhibitory potency observed experimentally. The identification of these lead compounds was the result of the synthesis of a very large number of compounds in which mainly diverse moieties that mimic the fatty acid chain of the substrate were explored.…”
Section: The Lpxc Enzymementioning
confidence: 99%
“…Notably, it is inactive against P. aeruginosa . Such a lack of activity against P. aeruginosa LpxC appeared to be caused by the rigidity of the P. aeruginosa enzyme, whereas the E. coli enzyme is conformationally dynamic and can undergo a conformational switch that expands the active site to accommodate inhibitors with various head groups, including compounds with opposite stereo centers at the Cα position next to the hydroxamate group [46] ( Fig. 3E ).…”
Section: Lpxcmentioning
confidence: 99%